A first course in statistics - McClave, James T.; Sincich, Terry (Upper Saddle River, N.J. : Pearson/Prentice Hall, 2009)
This introduction to statistics presents balanced coverage of both the theory and application of statistics and at the same time helps students to develop and enhance their critical thinking skills.
Keywords: Statistics